Ochratoxin A dietary exposure assessment in five food categories from Zhejiang Province - ZHAO Bi; WU Pinggu; ZHANG Ronghua; ZHAO Dong; ZHANG Hexiang; WU Xiaoli; CAI Zengxuan; CHEN Jiang; PAN Xiaodong; WANG Jikai; XU Jiaojiao; QI Xiaojuan; et al. (Zhongguo shipin weisheng zazhi, 2022)
ObjectiveTo evaluate the food exposure risk of ochratoxin A （OTA） in Zhejiang Province， China.MethodsA representative of 518 samples （five food categories including 24 kinds of food stuffs） were examined from 2018 to 2019 in order to evaluate the occurrence of OTA in Zhejiang Province. Food consumption data was collected from the Food Consumption Survey of Zhejiang Province between 2015 and 2016.ResultsOTA was only detected in grains and related products， but was not detected in fruits， tea， puffed foods and infant cereals. The higher incidence was found in oats and related products （16.1%，5/31）； the OTA levels of positive samples ranged from 0.53 to 4.00 μg/kg； and the maxium value of 4.00 μg/kg was found in oats and related products； no samples exceeded the limit set by China （5 μg/kg）. Exposure assessment showed that in most consumption scenarios， OTA probable daily intake for eating grains and related products were 0.004-7.360 ng/kg BW， less than OTA safety exposure value of 14 ng/kg BW； the highest OTA exposure value was 19.627 ng/kg BW and represents 140.19% of the safe intake. The 1-6 years old age group had the highest daily intake of 0.014-34.644 ng/kg BW， representing 0.10%-247.46% of the safe intake. The main food source of OTA was rice with a contribution rate of 87.22%-98.32% among different scenarios.ConclusionsThe OTA intakes through grains and related products consumption by Zhejiang population do not raise safety concerns except a few high intake groups， especially young consumers.